1993
DOI: 10.1007/bf02407357
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic relationships of HMG box DNA-binding domains

Abstract: HMG boxes were initially identified as DNA-binding domains of the human RNA polymerase I (pol I) transcription factor hUBF and the animal high-mobility-group (HMG) protein family HMG1. Since then, numerous sequences of HMG-box-containing HMG proteins and other DNA-binding proteins from several species have become available. By sequence comparisons of a selected range of HMG boxes from these proteins and the construction of phylogenetic trees we show that the HMG box is highly conserved between DNA-binding prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
20
0

Year Published

1993
1993
1997
1997

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 40 publications
3
20
0
Order By: Relevance
“…The immunological crossreactivity of V. faba H M G proteins and the insect c H M G l a protein together with the preferential binding of plant and insect H M G box containing H M G proteins to A/T-rich doublestranded DNA [17,31,32], indicates a closer relationship of the plant H M G proteins to the corresponding insect proteins, than to the vertebrate H M G proteins. This is consistent with the similarities of the primary structures of the plant and insect proteins [11 ] which, unlike the vertebrate HMG1 family, contain only a single HMGbox DNA-binding motif.…”
supporting
confidence: 70%
“…The immunological crossreactivity of V. faba H M G proteins and the insect c H M G l a protein together with the preferential binding of plant and insect H M G box containing H M G proteins to A/T-rich doublestranded DNA [17,31,32], indicates a closer relationship of the plant H M G proteins to the corresponding insect proteins, than to the vertebrate H M G proteins. This is consistent with the similarities of the primary structures of the plant and insect proteins [11 ] which, unlike the vertebrate HMG1 family, contain only a single HMGbox DNA-binding motif.…”
supporting
confidence: 70%
“…This represents the first clear evidence for HMG proteins binding to a plant ESR and is in contrast to recent findings in radish (Echeverria et al 1992), where proteins binding to the repeat region of radish ESR were found to be labile to a 2% TCA treatment and heat and hence probably do not represent HMG proteins. It could well be that, depending on the regulatory requirements for the expression of the rRNA genes, HMG proteins and presumed UBF-like factors compete for the binding sites in the ESR by use of their homologous HMG-boxes (Griess et al 1993).…”
Section: Discussionmentioning
confidence: 99%
“…Different proteins within the family have limited sequence similarity to one another even within the HMG boxes (45,46). Those regions that are conserved appear to be responsible for folding the three alpha helices of the HMG-box into an L-shape (47,48).…”
Section: Methodsmentioning
confidence: 99%